Devil's Needle & Other Tales of Vice and Redemption - Sauer, Rodney (Kino Classics, 2012)
"The Devil's Needle" stars silent superstar Norma Talmadge as Renee, a French artist's model who uses morphine as an escape from the dull reality of her life. She recommends it to a neurotic artist played by Tully Marshall (Queen Kelly), because ''it kindles the fires of genius.'' The artist quickly becomes addicted to the drug and the quality of his work begins to disintegrate. He takes on a new model, marries her, and starts her on the same path of moral degradation, until a guilt-ridden Renee decides to intervene in order to save them both. According to silent film historian Kevin Brownlow, "The Devil's Needle" was banned by the state of Ohio, but the censor board reversed its decision after recognizing the positive message beneath the film's scandalous surface. This special edition was mastered from a 35mm preservation print of the 1923 re-release version. The only known surviving copy, the element suffers significant nitrate decomposition during some scenes. [www.dvdbeaver.com]